The Failure of Exclusive Breastfeeding on The Incidence of Stunting Among Toddlers - Purnamasari, Anisa; Wa Ode Aisa Zoahira; Apriyanti, Apriyanti; I Wayan Romantika; Amzal Mortin Andas (Journal of Islamic Nursing, 2024)
Introduction: Stunting is caused by chronic and permanent nutritional deficiencies in the growth of toddlers. The World Health Organization has positioned Indonesia as the third country with the highest prevalence of stunting in Southeast Asia. In Southeast Sulawesi, stunting ranks fifth out of the ten provinces with the highest prevalence. The prevalence data of stunting in Southeast Sulawesi for children under five years old in 2022 was 27.7%. The number of stunted toddlers in Kendari City increased to 365 individuals in 2022, with the Puuwatu district showing the highest prevalence. Infant development is hindered due to insufficient nutritional intake, particularly exclusive breastfeeding. Failure in exclusive breastfeeding leads to long-term consequences. Objective: To assess the impact of the Failure of Exclusive Breastfeeding on the Incidence of Stunting Among Toddlers in the catchment area of Puuwatu Community Health Center. Methods: A cross-sectional research design was employed using a non-probability sampling method involving 84 respondents. Data collection was conducted using the Breastfeeding Self-efficacy Scale-Short Form (BSES-SF). Result: The research findings failure of exclusive breastfeeding variable is 0.044 < 0.05 for the mindset in breastfeeding indicator, 0.030 < 0.05 for the emotional reaction in breastfeeding indicator, and 0.005 < 0.05 for the breastfeeding behavior indicator, indicating a significant association between the Failure of Exclusive Breastfeeding and the Incidence of Stunting Among Toddlers in the catchment area of Puuwatu Community Health Center. Conclusion: Based on this research, the crucial role of Exclusive Breastfeeding in the growth and development of toddlers is emphasized, underscoring its significance as an integral element in the nursing care process administered by healthcare professionals. Keywords: Stunting, Exclusive Breastfeeding, Toddlers, Nursing, Southeast Sulawesi